ANALISIS IMPLEMENTASI MODEL TGT BERBANTUAN KARTU DOMINO KEBERAGAMAN BUDAYA UNTUK MENINGKATKAN KEAKTIFAN SISWA SD - Alfisyah; Helna, Hijjatul; Firza, Muhammad; Ferdiyansyah, Aldy; Mulya Budi Harsono, Arta; Hidayat, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the Teams Games Tournament (TGT) learning model supported by Cultural Diversity Domino Cards as an effort to enhance students’ activeness in Social Studies learning in Grade V at SDN Pengembangan 8 Banjarmasin. This research employed a qualitative approach with a case study design. The participants consisted of one teacher and 18 students. Data were collected through observation, interviews, and documentation, and analyzed using triangulation techniques to ensure data validity. The findings indicate that prior to the implementation of the TGT model, learning tended to be monotonous with low student participation. After the implementation of the TGT model combined with the Cultural Diversity Domino Card game, the classroom atmosphere became more active, interactive, and engaging. Students showed greater involvement in group activities, improved collaboration skills, and better understanding of cultural diversity content. The model also provided opportunities for previously passive students to participate more actively in the learning process. Therefore, the TGT model supported by Domino Cards proved to be effective in enhancing students’ activeness and learning experience in Social Studies at the elementary school level.